An empirical analysis of gold price in Malaysia / Muhammad Hisyamuddin Masdi - Masdi, Muhammad Hisyamuddin (2015)
Evidence from the volatility gold market shows that relationship of the gold price consistent with oil prices in the period since 2000 to 2015. Nevertheless, sometimes the volatility of gold price is not in line with oil price. This led a researcher to investigate the study of the relationship between gold prices and oil prices in Malaysia and to know whether it has causality on gold prices and oil prices. The main objective of this study is to investigate the relationship between gold price and oil price in Malaysia. Besides that, independent variable is taken to determine factor influence the gold price in Malaysia which exchanges rate, gross domestic product, and interest rate and to examine the causation between gold and oil price. The data has been collected starting from September 2000 to September 2015 in 174 months. The study uses time series data to get results and test using OLS, correlation, Johansen cointegration and Pairwise Granger causality test. The result of a relationship between gold price and the oil price has a positive relationship are found. There is significant between gold price and the oil price. Moreover, a result found the factor that influences gold price in Malaysia show gross domestic product has a significant positive relationship with the gold price. However; exchange rate and interest rate show a negative relationship with gold prices. Finally, the causality between gold price and oil price show the volatility of gold does Granger cause the oil price, but changes in oil price does not Granger cause the gold price.